Low rates of nucleoside reverse transcriptase inhibitor (NRTI) resistance detected in a well monitored cohort in South Africa accessing antiretroviral therapy - Wallis, Carole L (2011)
BACKGROUND: Emergence of complex HIV-1 drug resistance mutations has been linked to the duration of time on a failing antiretroviral (ARV) drug regimen. This study reports on resistance profiles in a closely monitored subtype C infected cohort. METHODS: A total of 812 participants were enrolled into the CIPRA-SA ‘safeguard the household’ study, viral loads (VLs) were performed 12 weekly for 96 weeks. Virological failure was defined as either <1.5 log drop in VL at week 12 or 2 consecutive VL measurements >1000 RNA copies/ml after week 24. Regimens prescribed were in-line with the South African roll-out program (d4T, 3TC, EFV or NVP). Viral RNA was extracted from patients with virological failure, and pol RT-PCR and sequence analysis were performed to determine drug resistance mutations. RESULTS: Eighty three participants experienced virological failure on the first-line regimen during the study period, of which 61 (73%) had HIV-1 drug resistance mutations. The M184V mutation was the most frequent (n=46; 65%), followed by K103N (46%) and Y181C (21%). TAMS were infrequent (1%) and Q151M was not observed. CONCLUSION: Drug resistance profiles were less complex than has been previously reported in South Africa using the same ARV drug regimens. This data suggests that frequent viral load monitoring limits the level and complexity of resistance observed in HIV-1 subtype C, preserving susceptibility to second-line options.